Characterizing the Natural Attenuation Potential of Chlorinated Ethenes Contaminated Sites - Carreon-Diazconti, Concepcion (The University of Arizona., 2006)
Site characterization methods for measuring the occurrence, magnitude, and rate of microbial mediated transformation processes were evaluated to assess the implementation of monitored natural attenuation (MNA) at chlorinated ethenes contaminated sites. A model site in Arizona, the Park-Euclid WQARF site in Tucson, was selected for the study. Field, geochemical, and compound specific carbon isotope fractionation (CSI) data confirm intrinsic biodegradation is occurring in the perched aquifer. Use of the BIOCHLOR model and a screening protocol support the potential for reductive dehalogenation found in the perched aquifer. Biotransformation of tetrachloroethene to cis-1,2-dichloroethene (cis-DCE) was achieved in microcosm studies. Transformation of cis-DCE to vinyl chloride and to ethene is, at the moment, the laboratory rate limiting step. PCR analysis established that the aquifer contains Dehalococcoides sp. and other dechlorinating microorganisms, though genes that encode for enzymes capable of achieving complete dehalogenation of the chlorinated contaminants were confirmed only in one monitoring well. The regional aquifer shows little evidence of intrinsic biodegradation. This study corroborates that CSI analysis can be used as an additional line of evidence to evaluate and verify MNA. Microbial analysis provides relevant information about the capabilities of native microbial communities to carry out reductive dehalogenation and thus, to naturally attenuate chlorinated compounds at a contaminated site. The combination of microcosm studies, CSI analysis, and bacterial DNA identification is becoming a convincing line of evidence for the assessment of MNA application to chloroethenes contaminated sites.